2015
DOI: 10.1002/jbio.201400145
|View full text |Cite
|
Sign up to set email alerts
|

An infrared sensor analysing label-free the secondary structure of the Abeta peptide in presence of complex fluids

Abstract: The secondary structure change of the Abeta peptide to beta‐sheet was proposed as an early event in Alzheimer's disease. The transition may be used for diagnostics of this disease in an early state. We present an Attenuated Total Reflection (ATR) sensor modified with a specific antibody to extract minute amounts of Abeta peptide out of a complex fluid. Thereby, the Abeta peptide secondary structure was determined in its physiological aqueous environment by FTIR‐difference‐spectroscopy. The presented results op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 61 publications
(65 reference statements)
2
85
0
1
Order By: Relevance
“…This was reflected in the performances of the different machine learning classifiers in the first and second step classifications. This biomarker can then be used for the diagnosis of the specific disease [43,76]. Similar to our previous study [1], the classification based on leukocytes spectra gave better success rates compared with the plasma (Figures S2 and Table S2).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This was reflected in the performances of the different machine learning classifiers in the first and second step classifications. This biomarker can then be used for the diagnosis of the specific disease [43,76]. Similar to our previous study [1], the classification based on leukocytes spectra gave better success rates compared with the plasma (Figures S2 and Table S2).…”
Section: Discussionsupporting
confidence: 79%
“…Many studies have reported that FTIR spectroscopy combined with multivariate analysis techniques is an efficient tool for the analysis and identification of different biological samples such as for early detection of cancers [40][41][42][43][44][45][46][47][48], neurological diseases [49,50] and bacterial susceptibility [51,52]. Recently, we successfully used FTIR spectroscopy to diagnose bacterial and viral infections using small samples of blood from patients [1].…”
Section: The T-cells Are Divided Into Two Types Helper T-cells (Cd +mentioning
confidence: 99%
“…1B reflects the secondary structure distribution of Ab or tau, respectively. Monomeric alpha-helical or disordered isoforms absorb between 1653 and 1649 wavenumbers (cm 21 ), whereas b-sheet isoforms absorb around 1626 cm 21 . Increased b-sheet content, which is characteristic for Ab and tau in AD pathology, shift the amide I band to lower wavenumbers.…”
Section: Resultsmentioning
confidence: 99%
“…In many applications, surface modification of the waveguiding structures is essential to provide molecular recognition interfaces that attract analyte molecules (e.g., proteins, peptides) to the waveguide surface (Figure 6). Depending on the material properties, such bio(organic) modifications take advantage of various binding motifs, including self-assembled monolayers, metal ion affinity and chelation mechanisms, amine coupling, antibody coupling, biotin-avidin linking, and his-tag coupling, thus enabling device technologies suitable for biodiagnostics (108)(109)(110)(111). Ideally, DNA-and aptamer-based functionalization facilitating selective yet label-free binding with high affinity and selectivity have been shown, for example, for bacterial lysates (112) (Figure 7).…”
Section: Figurementioning
confidence: 99%
“…For example, the aggregation state of α-synuclein or amyloid β (Aβ) peptides, which are both associated with neurodegenerative diseases such as Parkinson's or Alzheimer's, have been studied via MIR spectroscopy (110). Probing mechanistic details of misfolding and fibrillation (122,123), as well as the inhibition of these processes, along with potential environmental influences and stimulants has revealed band shifts characteristic of the amide I (1,600-1,700 cm −1 ) and amide II (1,500-1,600 cm −1 ) features of proteins, which may be assigned to α-helix or β-sheet conformations (124,125).…”
Section: Liquid Phase: Biomedical Applications and Process Monitoringmentioning
confidence: 99%